Meningkatkan Kualitas Pendidikan Islam Melalui Implementasi Teknologi Pendidikan - Mardiah Astuti; Herlina, Herlina; Ibrahim, Ibrahim; Isma Eka Wardana; Sofiyan Ardiansyah; Risma Oktariani (Student Scientific Creativity Journal, 2023)
This article discusses the importance of introducing educational technology in improving the quality of Islamic education. Islamic education has an important role in educating generations who are noble and capable. Educational technology can be utilized to increase the availability of Islamic educational resources. Students have easy access to high-quality and diverse Islamic learning materials through online learning platforms. In addition, educational technology allows for more active interactions between teachers and students. Teachers can assign assignments, submit materials, and provide direct feedback to students, encouraging personalized learning, and focusing on individual student needs. Educational technology also offers opportunities to further develop the professional skills of teachers in Islamic education. Teachers can take advantage of additional learning resources, expand collaborative networks with other teachers, and participate in professional training online. However, when implementing educational technology in Islamic teaching, care must be taken to ensure clear guidelines, adequate support, and a balance between the use of technology and traditional approaches to Islamic learning. The introduction of educational technology can be an effective way to improve the quality of Islamic education to produce a generation that is knowledgeable and able to make a positive contribution to society.